Contributions to the biology of the Philippine archipelago and adjacent regions - Bartsch, Paul; Van Name, Willard G.; Mayer, Alfred G.; Michael, Ellis L.; Bigelow, Henry B. (Govt. print. off., 1917)
contents: v.1 pt.1 The Philippine land shells of the genus Amphidromuspt.2 Ascidians from the Philippines and adjacent waters pt.3 Report upon the Scyphomedusae collected by the U.S. Bureau of Fisheries steamer "Albatross" in the Philippine islands and Malay archipelago. pt.4 Report on the Chaetognatha collected by the U.S. fisheries steamer "Albatross" during the Philippine expedition, 1907-1910. pt.5 Hydromedusae, Siphonophores and Ctenophores of the "Albatross" Philippine expedition